The Influence of Service Quality on Company Reputation - Muhyiddin Zainul Arifin; Ridwan Imanullah (INCOME: Innovation of Economics and Management, 2021)
Service quality is the key to success to be able to satisfy consumers because through good service then the company will give a good impression to consumers This type of research is quantitative, namely research methods based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, data analysis is quantitative/statistical, with the aim of testing predetermined hypotheses. Based on the level of explanation (level of clarity), this study uses associative analysis. Data collection techniques using questionnaires and interviews. The respondents of this study were students of KH.A.Wahab Hasbullah University totaling 100 people. The result of this research is that there is a significant influence between service quality and company reputation. The results of the measurement of simple linear regression analysis of 0.863 are included in the strong/high correlation. While the value of r square is 0.745, which means that the service quality variable contributes 74.5% influence on the company's reputation.